Interleukin-22 as a molecular adjuvant facilitates IL-17-producing CD8(+) T cell responses against a HBV DNA vaccine in mice - Wu, Bing (Landes Bioscience, 2013)
Interleukin-22 (IL-22) is mainly produced by activated Th1 cells, Th17 cells and NK cells and promotes anti-microbial defense, pro-inflammatory and tissue remodeling responses. However, its potential use as a vaccine adjuvant has not been tested. In this study, we tested if a DNA construct expressing IL-22 (pVAX-IL-22) could be used as a molecular adjuvant to enhance host immune responses induced by HBV DNA vaccination (pcD-S2). After immunizing mice with pcD-S2 combined with pVAX-IL-22, we didn’t find enhancement of HBsAg-specific antibody responses in comparison to mice immunized with pcD-S2 alone. However, there was an enhancement of the level of IL-17 expression in antigen specific CD8(+) cytotoxic T lymphocytes (Tc17). By using CD8 T-cell knockout (KO) and IL-17 KO mice, Tc17 cells were found to be a dominant population driving cytotoxicity. Importantly, there was a correlation between pVAX-IL-22 enhancement of T lymphocytes and a reduction of HBsAg-positive hepatocytes in HBsAg transgenic mice. These results demonstrate that IL-22 might be used as an effective adjuvant to enhance cellular immune responses during HBsAg DNA vaccination since it can induce Tc17 cells to break tolerance in HBsAg transgenic mice.